2021
DOI: 10.37939/jrmc.v25i3.1711
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Factors that Influence the Completion of the Thesis of Master of Health Professions Education Graduates: A Qualitative Study

Abstract: Objective: To investigate the experience of timely thesis completion by the graduates of the Master of Health Professions Education (MHPE) program in Pakistan.Study Design: Qualitative interpretative study design.Settings: Riphah University Islamabad and HITEC-IMS Taxila.Duration: May 2018 to June 2019.Materials and Methods: Data was collected by semi-structured interviews. All interviews were carried out in person. Detailed notes were taken, and conversations were audio-recorded. Three authors analyzed data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Intrinsic motivation has been reported as one of the most important factors in MHPE graduates for completing their thesis. 20 Without the right impetus, even after securing admission to an MHPE program, students joining the program as a last choice or applying because they considered it to be an easier program compared to others, may find it difficult to fulfill the necessary academic requirements for successful graduation or have the motivation to improve health science education. The findings showed that the factors that the authors of this study, as medical educationists, expected to be the most important for applicants in selecting the MHPE program turned out to be less significant than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic motivation has been reported as one of the most important factors in MHPE graduates for completing their thesis. 20 Without the right impetus, even after securing admission to an MHPE program, students joining the program as a last choice or applying because they considered it to be an easier program compared to others, may find it difficult to fulfill the necessary academic requirements for successful graduation or have the motivation to improve health science education. The findings showed that the factors that the authors of this study, as medical educationists, expected to be the most important for applicants in selecting the MHPE program turned out to be less significant than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the related work to this topic are focused on determining the factors that influence research project completion and non-completion, thus the works [11], [12] and [13] identified different factors such as motivation, ability to write scientific papers, guidance quality, commitment, diligence, communication skills, research experience among others.…”
Section: Related Workmentioning
confidence: 99%